Functional plant ecology - Pugnaire, Francisco I (Taylor & Francis, 2012)
Offers findings and research breakthroughs in plant ecology. This book investigates plant structure and behavior across the ecological spectrum. It features chapters on molecular ecology as well as the ecology and evolution of plant crowns. It includes a concluding chapter that addresses approaches to generalization in functional plant ecology.